Making Space for the Gods: Ethnographic Observations of Chinese House Temples in Singapore - Shawn Goh Ze Song (Religions, 2020)
Space for religious use is highly regulated in Singapore. Specific plots of land are reserved for religious groups to bid for, and create, “official” spaces of worship. However, religious practices continue to exist within “unofficial” sacred spaces, such as house temples and wayside shrines, negotiating and resisting the overt management of religion by the Singapore state. Scholars, including Vineeta Sinha and Terence Heng, demonstrate how sacrality infused into everyday secular urban spaces defies neat binaries of “sacred/profane” and “legal/illegal”, and how Chinese house temples or sintuas—temples located within public housing flats—sustain sacred spaces, despite being technically illegal under housing regulations. Drawing upon a series of ethnographic observations conducted over a year of four sintuas and their activities in Singapore, this paper explores the different ways through which sintuas produce sacred space as a response to spatial constraints imposed by the state. These include (1) re-enchanting everyday urban spaces during a yewkeng—a procession around the housing estate—with the help of a spirit medium; (2) using immaterial religious markers (e.g., ritual sounds and smells) to create an “atmosphere” of sacredness; (3) appropriating public spaces; and (4) leveraging the online space to digitally reproduce images of the sacred.